Nira Production In Terms Of Slope Level In South Tapanuli District - Darmadi Erwin Harahap; Retna Astuti Kuswardani; Tumpal HS Siregar; Muhammad Darwis (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
South Tapanuli is located at an altitude of 0 to 1,985 m above sea level, where almost at all levels of this altitude we will find sugar palm plants growing wild. The purpose of this study was to evaluate the relationship between slope gradient and sugar palm plant productivity in South Tapanuli Regency. The research method used was the field survey method on sugar palm stands used as sample plants with various levels of slope gradient. Furthermore, the data obtained in the field were tabulated and processed using linear regression. The results of the study showed that the slope gradient was negatively correlated with sap production, meaning that the higher the slope gradient, the lower the sap production. The highest sap production was found at an altitude of 400 - 800 meters above sea level with a slope gradient of 8 - 15% with a sap production of 14.27 liters / day.